Broadening the Variability for Peanut Breeding with a Wild Species-Derived Induced Allotetraploid - Taís Suassuna; Nelson Suassuna; Kennedy Martins; Ramon Matos; Jair Heuert; David Bertioli; Soraya Leal-Bertioli; Márcio Moretzsohn (Agronomy, 2020)
The use of wild species in peanut breeding provides remarkable opportunities for introducing new traits to the peanut crop and it has increased in recent years. Here, we report the morphological and agronomic, including disease resistance, variation observed in 87 Recombinant Inbred Lines (RILs) that were derived from the wild ancestors of peanut and the cultivar Runner IAC-886. These lines exhibited a wide range of variation for these traits, with transgressive segregation and novel phenotypes being observed in many lines. Quantitative Trait Loci (QTLs) for agronomic and resistance traits were detected. Six RILs with contrasting phenotypes for agronomic traits and moderate resistance to leaf spots were genotyped. All of the lines had, on average, 50% wild alleles, with at least one large wild segment and multiple interspersed alleles in all of the chromosomes. Genetic exchange between subgenomes was observed. On four lines, the top of Chr 05/15, which is tetrasomic AAAA in A. hypogaea, has been restored to its AABB state by the introgression of A. ipaënsis alleles. We identified lines with good agronomic traits while harboring genome composition and structure completely different from each other and from the cultivated peanut. The variation that is observed for the fruit type is also important for a better comprehension of the domestication process in peanut. This increase in genetic diversity has great potential benefits for the peanut breeding programs.